Hypotonic hyponatremia by primary polydipsia caused brain death in a 10-year-old boy - A Ra Ko; Soo Jung Kim; Mo Kyung Jung; Ki Eun Kim; Hyun Wook Chae; Duk Hee Kim; Ho-Seong Kim; Ah Reum Kwon (Korean Society of Pediatric Endocrinology, 2015)
Hypotonic hyponatremia by primary polydipsia can cause severe neurologic complications due to cerebral edema. A 10-year-and-4-month-old boy with a psychiatric history of intellectual disability and behavioral disorders who presented with chief complaints of seizure and mental change showed severe hypotonic hyponatremia with low urine osmolality (serum sodium, 101 mmol/L; serum osmolality, 215 mOsm/kg; urine osmolality, 108 mOsm/kg). The patient had been polydipsic for a few months prior, and this had been worse in the previous few days. A diagnosis of hypotonic hyponatremia caused by primary polydipsia was made. The patient was in a coma, and developed respiratory arrest and became brain death shortly after admission, despite the treatment. The initial brain magnetic resonance imaging showed severe brain swelling with tonsillar and uncal herniation, and the patient was declared as brain death. It has been reported that antidiuretic hormone suppression is inadequate in patients with chronic polydipsia, and that this inadequate suppression of antidiuretic hormone is aggravated in patients with acute psychosis. Therefore, hyponatremia by primary polydipsia, although it is rare, can cause serious and life-threatening neurologic complications.